Feeding Management and their Constraints in Dairy Bovines - Rajawat, Brijendra Singh; Hadiyal, Satish; Rathod, Ramesh; Rathod, Anshuman; Kumawat, Prabhu Dayal; Gaur, Mitesh; Tailor, S.P.; Yadav, M.C. (Indian Journal of Extension Education, 2018)
As data were collected from 360 farmers of rural area covering 12 villages of 4 tehsils of two districts. The farmers were equally distributed with respect to Karauli and Sawai Madhopur districts of eastern Rajasthan. The information was collected from respondents on adoption of feeding management practices and their constraints of dairy bovines by a questionnaire. The major feeding constraints in Karauli and Sawai Madhopur districts to the farmers had some important barriers in the adoption of ideal feeding management practices includes high prices of concentrate (2.63MS) followed by unavailability of concentrate and mineral mixture (2.43MS), shortage of feeds & fodders for animals (2.39MS) and lack of knowledge about balance ration (2.32MS). There is a need to provide knowledge of scientific feeding management practices by reducing feeding constraints through efficient livestock feeding management programme.
Keywords: Dairy bovines; feeding management